Answer:
![(\frac{6x^2y}{5})](https://tex.z-dn.net/?f=%28%5Cfrac%7B6x%5E2y%7D%7B5%7D%29)
Step-by-step explanation:
Given
![\frac{(2x)(3x^3y^2)}{5x^2y}](https://tex.z-dn.net/?f=%5Cfrac%7B%282x%29%283x%5E3y%5E2%29%7D%7B5x%5E2y%7D)
Required
Solve
Open the brackets
= ![\frac{(2x*3x^3y^2)}{5x^2y}](https://tex.z-dn.net/?f=%5Cfrac%7B%282x%2A3x%5E3y%5E2%29%7D%7B5x%5E2y%7D)
= ![\frac{(6x^4y^2)}{5x^2y}](https://tex.z-dn.net/?f=%5Cfrac%7B%286x%5E4y%5E2%29%7D%7B5x%5E2y%7D)
Apply law of indices:
= ![\frac{(6x^{4-2}y^{2-1})}{5}](https://tex.z-dn.net/?f=%5Cfrac%7B%286x%5E%7B4-2%7Dy%5E%7B2-1%7D%29%7D%7B5%7D)
= ![\frac{(6x^2y)}{5}](https://tex.z-dn.net/?f=%5Cfrac%7B%286x%5E2y%29%7D%7B5%7D)
= ![(\frac{6x^2y}{5})](https://tex.z-dn.net/?f=%28%5Cfrac%7B6x%5E2y%7D%7B5%7D%29)
Answer:
The correct answer is
Z⁶Y³/Z⁶Y⁴ = 1/Y
Step-by-step explanation:
<u>Points to remember</u>
1). xᵃ * xᵇ = xᵃ⁺ᵇ
2). xᵃ/xᵇ = xᵃ⁻ᵇ
3). x° = 1
4). x⁻ᵃ = 1/xᵃ
The given expression is Z⁶Y³/Z⁶Y⁴
<u>To find the simplification of expression</u>
Z⁶Y³/Z⁶Y⁴ = Z⁶⁻⁶ * Y³⁻⁴
= Z° * Y⁻¹ = 1 * 1/Y = 1/Y
Therefore the value of given expression Z⁶Y³/Z⁶Y⁴ is 1/Y
Answer:
49200
114800
32800
Step-by-step explanation:
196800/12=ans
ans * 3
ans * 7
ans * 2
Ooh, scary math
n+2b=67.5
n=27
27+2b=67.5
minus 27 both sides
2b=40.50
divide both sides by 2
b=20.25
a bracelet costs $20.25
2/10
20/100
Times 1/5 by 2 on both sidez and then times that by ten to get the second answer